The learning-teaching nexus: modelling the learning-teaching relationship in higher education - Knewstubb, Bernadette (Studies in higher education (Dorchester-on-Thames), 2016)
The teaching-learning relationship is often described as a conversation. However, many models of teaching and learning depict the worlds of teacher and learner as enclosed and inaccessible, linked by apparently transferred communicative meanings. A new interdisciplinary learning-teaching nexus (LTN) model combines perspectives from higher education, linguistic pragmatics and Gadamerian hermeneutics to conceptualise the learning-teaching nexus as a communicative relationship. The LTN model depicts teaching and learning as simultaneously individual experiences, affected by personal epistemological, contextual and situational assumptions, and a shared communicative space, in which communicators and their addressees work to reach mutual understandings. This paper outlines the LTN model, explaining how it extends earlier frameworks, and discusses implications for educational practice and future research.